UNGKAPAN KEPERCAYAAN RAKYAT DALAM UPACARA PENYELENGARAAN JENAZAH DI KENAGARIAN SELAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Riri Purnama Sari; Novia Juita; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2014)
This research was done to describe of form, meaning, and function of the expression the human’s trust in ceremony of corpse management in Nagari Selayo Kecamatan Kubung Kabupaten Solok. Data of this research were form, meaning and functions of the expression the human’s trust in Minangkabau especially in Kanagarian Selayo Kecamatan Kubung Kabupaten Solok. The data was collected trough interview and then, recorded the result of interview with some informant in Kenagarian Selayo Kecamatan Kubung Kabupaten Solok. In this research, it was found three results. The first, in Kanagarian Selayo Kecamatan Kubung Kabupaten Solok have 41 expressions of human’s trust in ceremony of corpse management. The second, in Kanagarian Selayo Kecamatan Kubung Kabupaten Solok have 41 expressions with implicit meaning that was got from orally and explicit meaning that was got from comprehended of the meaning in written. The third, the function of expressions human’s trust in ceremony of corpse management in Nagari Selayo Kecamatan Kubung Kabupaten Solok. The expression of human’s trust in ceremony of corpse management in Nagari Selayo Kecamatan Kubung Kabupaten Solok was divided into four parts. First, when the corpse at home has 23 expressions. Second, when the corpse bathed have 6 expressions. Third, when the corpse prayed have 1 expression. Fourth, when in the grave have 11 expressions.